Hexahelix Collaboration and Inclusive Disaster Governance: A CSR-Based Social Innovation through SINAR PELITA in Aceh Tamiang, Indonesia - Damelia, Winda; Chaerani, Tiara; Diltha, Khairunnisa; Alfaruk, Fahmi Abdullah; Rahmadani, Rara Ayuni (Pelopor Publikasi Akademika, 2025)
This study analyzes the implementation of Corporate Social Responsibility (CSR) by PT Pertamina EP Rantau Field through the program SINAR PELITA (Sistem Inklusif dan Responsif Pelibatan Difabel dalam Tanggap Bencana / Inclusive and Responsive System for Disability Engagement in Disaster Response) as a pioneering social innovation in Aceh Tamiang. Using the Socio-Ecological Framework (SEF) and the concept of hexahelix collaboration, this research investigates how multi-level vulnerabilities faced by persons with disabilities in disaster contexts are addressed through multi-actor partnerships. The findings demonstrate that vulnerabilities are not merely individual but span interpersonal, community, institutional, environmental, and policy levels. SINAR PELITA responds through integrated interventions such as the establishment of SATGAS DIGDAYA (Disability Task Force for Disaster Preparedness and Empowerment), the formulation of an Inclusive Disaster Response SOP, development of inclusive shelters, and the innovation of an evacuation electric boat. These outputs are achieved through the synergy of six key actors—industry, government, academia, community, media, and policy—forming a collaborative ecosystem in disaster risk reduction.This study contributes theoretically by demonstrating how CSR can evolve from philanthropic practices into transformative social innovation, positioning persons with disabilities as active agents of community resilience. Practically, SINAR PELITA represents a best practice model of inclusive disaster governance that can be replicated in other disaster-prone regions, while supporting the achievement of the Sustainable Development Goals (SDGs), particularly Goal 11 (Sustainable Cities and Communities) and Goal 13 (Climate Action).